On well p-embedded subgroups of finite groups - Hutsko, N.V.; Skiba, A.N. (Algebra and Discrete Mathematics, 2008)
Let G be a finite group, H a subgroup of G and HsG the subgroup of H genarated by all those subgroups of H which are s-permutable in G. Then we say that H is well p-embedded in G if G has a quasinormal subgroup T such that HT=G and T∩H≤HsG. In the present article we use the well p-embedded groups to obtain new characterizations for some class of finite soluble, supersoluble, metanilpotent and dispersive groups.